2019
DOI: 10.1038/s41477-019-0440-x
|View full text |Cite
|
Sign up to set email alerts
|

Bipartite anchoring of SCREAM enforces stomatal initiation by coupling MAP kinases to SPEECHLESS

Abstract: Cell-fate in eukaryotes is controlled by MAP Kinases (MAPKs) that translate external cues to cellular responses. In plants, two MAPKs, MPK3/6, regulate diverse processes of development, environmental response, and immunity. Yet, the mechanism bridging these shared signaling components with a specific target remains unresolved. Focusing on the development of stomata, epidermal valves for gas exchange and transpiration, we report here that the bHLH protein SCREAM functions as a scaffold recruiting MPK3/6 to down… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 62 publications
0
54
0
Order By: Relevance
“…Previous research has suggested that the phyB regulated transcription factor, PHYTOCHROME INTERACTING FACTOR 4, is involved in light mediated stomatal development [12]. Recent studies that have shown that ICE1 is a target of COP1 and ICE1's pivotal role in regulating SPCH could account for some aspects of light mediated stomatal development [8,35]. As photoreceptor signalling is known to work through both transcriptional and post-translation regulation [8,12,35], therefore it is probable that light mediated stomatal development is also regulated by both mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has suggested that the phyB regulated transcription factor, PHYTOCHROME INTERACTING FACTOR 4, is involved in light mediated stomatal development [12]. Recent studies that have shown that ICE1 is a target of COP1 and ICE1's pivotal role in regulating SPCH could account for some aspects of light mediated stomatal development [8,35]. As photoreceptor signalling is known to work through both transcriptional and post-translation regulation [8,12,35], therefore it is probable that light mediated stomatal development is also regulated by both mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These transcription factors form dimers with the bHLH proteins ICE1 and SCRM2 to regulate target genes [6]. A ligand/receptor/MAP kinase pathway negatively regulates stomatal development by targeting the SPCH-ICE1 dimer [7,8]. Stomatal lineage cells produce secreted peptides (EPF1 & EPF2), which bind a receptor complex that includes members of the ERECTA family (ERf), the TOO MANY MOUTHS (TMM) receptor-like protein and members of the SERK family of receptor kinases [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research of Kidokoro et al (2020) and several early studies (Chinnusamy et al 2003; Lee et al 2005) relied on the dominant ice1‐1 mutant. A recent study showed that the R236H mutation in the ice1‐1 mutant enhances the stability of ICE1 because the mutation disrupts the interaction of ICE1 with its negative regulators MPK3 and MPK6 (Putarjunan et al 2019). The effect of this dominant mutation on the cold response, however, appears to be complicated because it also affects the activity of ICE1 as a transcription factor (Chinnusamy et al 2003).…”
Section: Accession Numbermentioning
confidence: 99%
“…Interestingly, although the phosphorylation of SPCH is known to be mediated by mitogenactivated protein kinase 3/6 (MPK3/6), a direct interaction between MPK3/6 and SPCH has not been detected to date. A recent study has found that ICE1/SCRM2 acts as a scaffolding partner for their interaction (Lampard et al, 2008;Putarjunan et al, 2019). The direct association of MPK3/6 and ICE1/SCRM2 is also required for the phosphorylation and consequent degradation of ICE1/SCRM2, and this process is crucial for the proper specification of the stomatal cell fate (Putarjunan et al, 2019).…”
Section: Spch Integrates Intralineage Signals For Proper Stomatal Denmentioning
confidence: 99%